A process evaluation of the Philippine Alternative Learning System - Jose Ramon G. Albert; Ronald U. Mendoza; Deanne Lorraine D. Cabalfin; Mohammad A. Mahmoud; Mika S. Mu\~noz (Philippine Institute for Development Studies (PIDS), 2024)
This study presents a comprehensive process evaluation of the Department of Education's Alternative Learning System (ALS) in the Philippines, examining its effectiveness in providing second-chance education opportunities for out-of-school youth and adults (OSYAs). While the ALS plays a vital role in the Philippine education system, systematic evidence on its implementation effectiveness, operational processes, and institutional capabilities has thus far been limited. The study employs a mixed-methods approach, combining quantitative analysis of administrative data, key informant interviews, focus group discussions, and an online survey of 4,933 ALS past and current learners. This multi-faceted methodology provides both broad insights into system-wide patterns and granular understanding of implementation challenges. The evaluation reveals significant institutional strengths, particularly in teacher dedication and program adaptability. However, severe resource constraints hamper program effectiveness. Key findings demonstrate that the ALS faces significant operational constraints. Most notably, despite serving 0.8 percent of basic education learners, ALS receives only 0.1 percent of DepED's budget. This resource disparity manifests in concerning ways: a pupil-teacher ratio of 75:1 (compared to an ideal 25:1), inadequate facilities with 61 percent of Community Learning Centers below standard size requirements, and limited learning materials. Results from the online survey reveal high satisfaction with teaching quality (95%), though only 54 percent of program completers are employed, with 51 percent reporting high job-skill alignment. Work-study balance emerges as a significant challenge, particularly for working learners (45%), while financial difficulties affect 22 percent of participants. Gender disparities are notable, with female employment rates lagging significantly behind males, particularly in the 25-35 age group (34% versus 65%). The analysis also examines trends in the out-of-school youth population, considering the complementary effects of other interventions like the Pantawid Pamilyang Pilipino Program (4Ps). Projections suggest this population could decrease to approximately 500,000 by 2035, requiring strategic recalibration of the ALS program's scope and delivery models. This potential reduction raises fundamental questions about the program's "endgame" - specifically, what constitutes a manageable level of out-of-school youth based on Philippine context and international standards. The recommendations emphasize the need for increased funding, improved resource allocation, enhanced teacher training, stronger coordination among stakeholders, and innovative approaches to curriculum design and delivery. Additionally, the study calls for better alignment between ALS and other social protection programs, clearer metrics for measuring program effectiveness, and more targeted support for working learners and female participants. These findings are expected to inform evidence-based policymaking and catalyze strategic reforms to enhance the accessibility, quality, and relevance of alternative education in the Philippines.
Keywords: 330; alternative education; out-of-school youth; program evaluation; educational governance; implementation efficiency; Philippines